Penentuan Akar Persamaan Tak Linier Menggunakan Metode Prediktor-Korektor Halley - Khairil Amri; Minora Longgom Nasution; Riry Sriningsih (UNIVERSITAS NEGERI PADANG, 2021)
Abstract-Nonlinear equation which is difficult to solve by analysis, but it can be solved using approach of variety of numerical methods, for instance Newton-Raphson and Halley Methods. However, the methods are not guaranteed to be convergent. Predictor Corrector Halley's method is one of the method that appear from the advantages and disadvantages of Newton-Raphson and Method of Halley. This method uses the Newton-Raphson Method as predictor and Halley's Method as corrector. It has a higher order and more efficient from Newton-Raphson and Halley methods. The advantage of this method has a higher convergence that has sixth-order convergence so that the step of the iteration is fewer. Next,an algorithm of this method is used to determine the root approximations of nonlinear equations.Key Words-Non Linear Equations, Newton Method, Halley Method, Prediktor Corector Halley Method, Algorithm.